1996
DOI: 10.1046/j.1365-2958.1996.6331356.x
|View full text |Cite
|
Sign up to set email alerts
|

Protein F2, a novel fibronectin‐binding protein from Streptococcus pyogenes, possesses two binding domains

Abstract: Binding of the group A streptococcus (GAS) to respiratory epithelium is mediated by the fibronectin (Fn)-binding adhesin, protein F1. Previous studies have suggested that certain GAS strains express Fn-binding proteins that are different from protein F1. In this study, we have cloned, sequenced, and characterized a gene (prtF2) from GAS strain 100076 encoding a novel Fn-binding protein, termed protein F2. Insertional inactivation of prtF2 in strain 100076 abolishes its high-affinity Fn binding. prtF2-related g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
111
0
1

Year Published

1996
1996
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(117 citation statements)
references
References 28 publications
5
111
0
1
Order By: Relevance
“…Jaffe et al (8) reported that a highly homologous repeat domain in protein F2 is the main Fn-binding region when compared with that of protein F1. The present results showed that the putative Fn-binding domain of FbaB was highly conserved at the C-terminal region (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Jaffe et al (8) reported that a highly homologous repeat domain in protein F2 is the main Fn-binding region when compared with that of protein F1. The present results showed that the putative Fn-binding domain of FbaB was highly conserved at the C-terminal region (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that several surface proteins have binding abilities to human host proteins, such as fibronectin (Fn) (1), laminin (2), plasmin (3), collagen (4), immunoglobulins (5), and C4b (6). Fn-binding proteins of GAS have also been reported to be adhesins and invasins, including protein F1/SfbI (1, 7), protein F2 (8), SfbII/ SOF (9, 10), PFBP (11), and Fba (renamed FbaA) (12). It is interesting to note that each Fn-binding protein is distributed in a particular group of M serotype (7,12,13), and highly virulent GAS strains possess one or more Fn-binding proteins.…”
mentioning
confidence: 99%
“…In S. pyogenes, adherence could be mediated by different surface exposed proteins, which include among others, fibronectin binding proteins (FBPs) [7][8][9][10][11][12]. Four FBPs (SfbI, OF, PrtFII and Fbp54) have been extensively studied.…”
Section: Introductionmentioning
confidence: 99%
“…Group A streptococci possess a number of surface adhesins capable of interacting with the extracellular host protein fibronectin (Courtney et al, Downloaded from www.microbiologyresearch.org by IP: 54.191.190.102 On: Sat, 12 May 2018 15:00:43 C. M. GILLEN and OTHERS 1996 ;Jaffe et al, 1996 ;Kreikemeyer et al, 1995 ;Talay et al, 1992 ;Rocha & Fischetti, 1999 ;Hanski & Caparon, 1992), an interaction which has been shown to play a major role in the adherence of the streptococcal cell to the epithelial cells of the host (Talay et al, 1992 ;Courtney et al, 1996 ;Molinari et al, 1997). The streptococcal serum opacity factor (SOF ; SfbII) is a large extracellular and surface-bound protein of group A streptococci which is capable of binding fibronectin (Rakonjac et al, 1995 ;Kreikemeyer et al, 1999).…”
Section: Abbreviationsmentioning
confidence: 99%